2013
DOI: 10.1017/s0025315412001981
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the black goby, Gobius niger (Teleostei: Gobiidae), in the Gulf of Gabès (Tunisia, Central Mediterranean)

Abstract: The black goby Gobius niger (Linnaeus, 1758) (Gobiidae) is one of the most common gobies in southern Tunisian waters. This study provides the first detailed information on the reproductive biology of the G. niger in these areas. Samples of G. niger were collected by trawl from the Gulf of Gabès (Tunisia) between February 2009 and January 2010. A total of 1055 specimens were examined, ranging from 6.4 to 15.7 cm total length. The sex-ratio was in favour of males, especially in larger size-classes. The macroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The annual variations in the HSI showed that energy storage decreased after reproduction. Storage of fat within the liver during the reproductive period is a strategy adopted by many species in the Gulf of Gabes such as Diplodus vulgaris (Geoffroy Saint-Hilaire, 1817) (Hadj Taieb et al ., 2012) and Gobius niger (Linnaeus, 1758) (Hajji et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The annual variations in the HSI showed that energy storage decreased after reproduction. Storage of fat within the liver during the reproductive period is a strategy adopted by many species in the Gulf of Gabes such as Diplodus vulgaris (Geoffroy Saint-Hilaire, 1817) (Hadj Taieb et al ., 2012) and Gobius niger (Linnaeus, 1758) (Hajji et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Norway, Netherlands, Portugal, France, Italy), reproduction biology, age and growth of the black goby were reported by different authors (Vaas et al, 1975;Fabi & Giannetti, 1983;Nash, 1984;Arruda et al, 1993;Joyeux et al, 1991;Silva & Gordo, 1997;Bouchereau & Guelorget, 1998;Immler et al, 2004). Reproductive biology of the black goby in the Mediterranean, Gulf of Gabès, Tunisia was also studied by Hajji et al (2013). Moreover, studies on the black goby in the coast of Turkey were carried out on their age, growth and reproduction biology in the Bay of Izmir, Aegean Sea (Özaydın et al, 2007;Kınacıgil et al, 2008;Filiz & Toğulga, 2009) and in the Sea of Marmara (Kırdar & İşmen, 2018).…”
Section: Introductionmentioning
confidence: 89%
“…In other black goby populations, both smaller and larger in size than our study, Lm was estimated as 4.3 cm TL in males and 5.4 cm in females (about 7 to 12-13 months) in the Mauguio lagoon, France (Joyeux et al, 1991), as 6.0 cm TL (0 + age) in the Ria de Aveiro lagoon, Portugal (Arruda et al, 1993), as 7.8 TL cm about 0.86 years for females in the Izmir Bay, Turkey (Filiz & Toğulga, 2009) and 9.4 cm TL at one year in the Marmara Sea, Turkey (Kırdar & İşmen, 2018). In the Gulf of Gabès (Tunisia, Mediterranean), Lm was estimated as 10.1 cm TL in males and 9.7 cm in females (Hajji et al, 2013).…”
Section: Spawning Period and Size At Sexual Maturitymentioning
confidence: 99%
“…Black goby requires coarse substrates to have shelters for nest construction (Vaas et al 1975;Wiederholm, 1987;Mistri et al, 2000;Leatemia et al, 2017). The vegetated habitats are important for the abundance of marine macroinvertebrates which are the main prey resource for the black goby (Hajji et al, 2013;Matern et al, 2021). Vegetation cover also limits predation by increasing the complexity of the habitats (Heck and Orth, 1980;Kulczycki et al, 1981).…”
Section: Spatial and Temporal Distribution Of Gobius Niger In The Mar...mentioning
confidence: 99%